Владимир Соловьев и его время - Лосев Алексей Федорович (Жизнь замечательных людей, 2000)
Экземпляры: (20211022) / Инвентарный номер: 28788 / Цена: 80.00 / Сис.шифр: 87.3(2) / Авт.знак: Л 79 / ГРНТИ: 02 / ББК: 87.3(2)